ANALISIS DAMPAK PEMBELAJARAN DARING TERHADAP KEAKTIFAN BELAJAR SISWA KELAS V SDI BANI HASYIM SINGOSARI MALANG - Nur Ita; Muhammad Sulistiono; Ika Ratih Sulistiani (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The.background.for.researchers.to.research.and.examine.how.the.impact.of.online.learning.on.the.learning activities of fifth graders at SDI Bani Hasyim Singosari Malang. The problems studied in this study were what were the impacts of.online.learning.during.the covid-19.pandemic.for.fifth.graders.at.SDI Bani Hasyim Singosari Malang and how active the learning process was through online.learning.during.the.covid-19.pandemic.for.fifth graders at SDI Bani Hasyim Singosari Malang. The type of research used is qualitative, data collection procedures using the method of observation, interviews and documentation. The results showed that there were several negative impacts of.online.learning.during.the.covid-19.pandemic.for.fifth.grade.students.at SDI Bani Hasyim, namely, students understanding of material decreased, students social attitudes were reduced, students were dependent on gadgets and ineffective learning. Then as for the learning activities of the fifth grade students of SDI Bani Hasyim during online learning, namely, active attendance, active question and answer and activity collecting assignments. During online learning, class V students in terms of activity did not experience a decrease, it was the same as offline learning. Keywords: Impact, Online Learning, Learning Activity